2018
DOI: 10.1177/1479972318809472
|View full text |Cite
|
Sign up to set email alerts
|

The effect of comorbidity severity on pulmonary rehabilitation outcomes in chronic obstructive pulmonary disease patients

Abstract: Chronic obstructive pulmonary disease (COPD) is not only associated with respiratory system involvement but also with systemic consequences leading to chronic comorbidities. In this study, we aimed to investigate the effect of comorbidity severity on pulmonary rehabilitation (PR) outcomes in COPD patients. We conducted a retrospective cohort study to compare the effectiveness of PR in COPD patients who completed an 8-week PR program. There were at least one comorbid in 120 of 211 patients and we divided them i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…A large retrospective analysis found that multiple co‐morbidities and selected conditions such as heart and metabolic diseases adversely affected gains in exercise capacity and QOL following PR . However, other retrospective and prospective studies suggest the total number of co‐morbidities does not clearly adversely impact PR outcomes . Among 316 patients enrolled in PR, 62% reported co‐morbidities, and 45% of those had gains equal to or greater than the published MCID values for 6MWD, MRC dyspnoea scores and QOL .…”
Section: Additional Considerations For Patient Selection For Prmentioning
confidence: 97%
“…A large retrospective analysis found that multiple co‐morbidities and selected conditions such as heart and metabolic diseases adversely affected gains in exercise capacity and QOL following PR . However, other retrospective and prospective studies suggest the total number of co‐morbidities does not clearly adversely impact PR outcomes . Among 316 patients enrolled in PR, 62% reported co‐morbidities, and 45% of those had gains equal to or greater than the published MCID values for 6MWD, MRC dyspnoea scores and QOL .…”
Section: Additional Considerations For Patient Selection For Prmentioning
confidence: 97%
“…Exercise capacity. Nineteen studies (20 reports) (35,40,41,43,(62)(63)(64)(65)(66)(67)(68)(69)(70)(71)(72)(73)(74)(75)(76)(77) reported measures of exercise capacity with clinically significant improvements following exercise rehabilitation in 6MWD (35,67,68), VO 2 peak (62, 64, 66, 70, 75, 76), metabolic equivalents (41,66,77), HR recovery (71), maximal symptom limited incremental cycle ergometer time (73) and peak HR (71).…”
Section: Exercise Rehabilitation In Cohort/quasi-experimental Studiesmentioning
confidence: 99%
“…Symptoms. Three studies (62,65,69) reported symptom measures with no clinically significant improvements following exercise rehabilitation.…”
Section: Exercise Rehabilitation In Cohort/quasi-experimental Studiesmentioning
confidence: 99%